Partisipasi Pemilih Pemula Pada Pemilihan Kepala Daerah di Kota Magelang - Heniasari, Radeva Desika; Aliftania, Desti; Adzania, Keisya Hilda; Setiawan, Dandi; Nugraha, Joko Tri (FIA Unkris Press, 2025)
This study aims to examine the participation of first-time voters in the regional head elections in Magelang City using a quantitative approach. The main objective is to explore the motivations, political awareness, role of political socialization, and the challenges faced by young voters in exercising their voting rights. Data were collected through questionnaire surveys and literature reviews of political socialization activities conducted by educational institutions, social media, and electoral bodies. The findings reveal that the majority of first-time voters possess a strong normative awareness of the importance of participating in elections. However, obstacles such as low political literacy, limited access to credible information, and skepticism toward political processes remain significant challenges. Political socialization, particularly through schools and social media, plays a vital role in shaping the perceptions and motivations of the younger generation. This study recommends the implementation of collaborative and continuous strategies that involve schools, electoral institutions, and community leaders to improve the quality of political participation among first-time voters. Strengthening this engagement is essential to building a more inclusive, empowered, and participatory local democracy.